Experiences of mental health factors among domestic and international health professions students: a qualitative study at universities in China - Ling Jing; Wen Zhang; Diane P. Lee; Meng Sun; Guowei Wu; Xuan Ouyang; Zhening Liu (Mental Wellness, 2026)
Health professions students at Chinese universities experience a higher prevalence of mental illness than their peers in other professions, but few studies have qualitatively assessed students’ perceptions of their mental health risks. This study describes domestic and international health professions students’ experiences of risk factors to their mental wellness at Chinese universities. A total of 22 semi-structured interviews were conducted at 7 universities throughout China from April to July 2016. The 40 students interviewed identified academic stressors, work environment concerns, demographic disparities, relationships with peers, independent living, family expectations, and stigma toward mental illness as factors that were associated with their mental health in university. International students also experienced difficulties with learning Chinese and living in a new country. In China, health professions students’ experiences of mental health involve a complex combination of factors relating to competition, gaining independence, building relationships, and diverse identities, some of which are unique to their training and others which reflect the university environment or challenges for their generation. Institutional and societal changes that address these factors could benefit the mental wellness of China’s future healthcare workforce.